Melatonin‐enhanced autophagy protects against neural apoptosis via a mitochondrial pathway in early brain injury following a subarachnoid hemorrhage. Issue 1 (28th August 2013) - Chen, Jingyin; Wang, Lin; Wu, Cheng; Hu, Qiang; Gu, Chi; Yan, Feng; Li, Jianru; Yan, Wei; Chen, Gao
Abstract Melatonin is a strong antioxidant that has beneficial effects against early brain injury (EBI) following a subarachnoid hemorrhage (SAH) in rats; protection includes reduced mortality and brain water content. The molecular mechanisms underlying these clinical effects in the SAH model, however, have not been clearly identified. This study was undertaken to determine the influence of melatonin on neural apoptosis and the potential mechanism of these effects in EBI following SAH using the filament perforation model of SAH in male Sprague Dawley rats. Melatonin (150 mg/kg) or vehicle was given via an intraperitoneal injection 2 hr after SAH induction. Brain samples were extracted 24 hr after SAH. The results show that melatonin treatment markedly reduced caspase‐3 activity and the number of TUNEL‐positive cells, while the treatment increased the LC3‐II/LC3‐I, an autophagy marker, which indicated that melatonin‐enhanced autophagy ameliorated apoptotic cell death in rats subjected to SAH. To further identify the mechanism of autophagy protection, we demonstrated that melatonin administration reduced Bax translocation to the mitochondria and the release of cytochrome c into the cytosol. Taken together, this report demonstrates that melatonin improved the neurological outcome in rats by protecting against neural apoptosis after the induction of filament perforation SAH; moreover, the mechanism of these antiapoptosis effects was related to the enhancement of autophagy, which ameliorated cell apoptosis via a mitochondrial pathway.